2017
DOI: 10.1177/1010428317725923
|View full text |Cite
|
Sign up to set email alerts
|

Signature of genetic associations in oral cancer

Abstract: Oral cancer etiology is complex and controlled by multi-factorial events including genetic events. Candidate gene studies, genome-wide association studies, and next-generation sequencing identified various chromosomal loci to be associated with oral cancer. There is no available review that could give us the comprehensive picture of genetic loci identified to be associated with oral cancer by candidate gene studies-based, genome-wide association studies-based, and nextgeneration sequencing-based approaches. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 83 publications
0
16
0
1
Order By: Relevance
“…It is widely accepted that HNSCC occurs as a result of cumulative genetic/epigenetic abnormalities in cancer-associated genes. However, to date, a limited number of genes have been reported as candidate somatic drivers for HNSCC, including tumor protein p53 (19), Akt1, APC, CCND1, fibroblast growth factor receptor 3 (FGFR3), NOTCH1, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PI3KCA), and phosphatase and tensin homolog (PTEN) (20)(21)(22)(23)(24). In addition, the HNSCC-specific cancer-associated genes/pathways are not well illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that HNSCC occurs as a result of cumulative genetic/epigenetic abnormalities in cancer-associated genes. However, to date, a limited number of genes have been reported as candidate somatic drivers for HNSCC, including tumor protein p53 (19), Akt1, APC, CCND1, fibroblast growth factor receptor 3 (FGFR3), NOTCH1, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PI3KCA), and phosphatase and tensin homolog (PTEN) (20)(21)(22)(23)(24). In addition, the HNSCC-specific cancer-associated genes/pathways are not well illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies identified MLL2 as a frequent mutated gene in congenital heart diseases and developmental diseases, such as Kabuki syndrome, for alternating of epigenetic and transcriptional regulation by nonsense mutating, splice‐site mutating, small deleting or inserting, and missense mutating . MLL2 also involved into the carcinogenesis of oral cancer by next‐generation sequencing (NGS), specifically, frequently altered in gingivo‐buccal oral squamous cell carcinoma . MLL2 also disrupt enhancer activity and transcription of genes to destruct cell stability during carcinogenesis …”
Section: Discussionmentioning
confidence: 99%
“…13 This polymorphic locus was reported to be involved in the occurrence of different cancers and the tumor diffusing capacity. [14][15][16][17][18] However, the findings of these studies are inconclusive because of small population sizes, genetic heterogeneity of samples, and other forms of possible confounding bias.…”
Section: Objectivesmentioning
confidence: 99%